Is It Good to Be a Green Multinational Bank? - Laguir, Issam; Stekelorum, Rebecca; Laguir, Lamia; Elbaz, Jamal (Management international / International Management / Gestiòn Internacional, 2020)
This paper examines the influence of environmental corporate social responsibility (ECSR) on corporate financial performance (CFP) using data on French multinational banks from 2008 to 2011. Our results show that the relationship between ECSR and multinational bank CFP is positive and statistically significant. However, taking into account R&D activities allows an alternative perspective: the influence of ESCR on ROA decreases as banks’ R&D activities increase. Thus, ECSR most strongly influences CFP in low-R&D intensity multinational banks.